2018
DOI: 10.1016/j.jpainsymman.2018.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Standard for Hospital-Based Palliative Care Consultation Teams in Japan Using a Modified Delphi Method

Abstract: We developed a standard for PCCTs in Japanese cancer hospitals. This standard provides a useful guide for clinical activities and a tool to evaluate quality of palliative care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…The barriers and challenges associated with palliative care development for PPC in LMICs include a lack of medical staff, lack of specialist education, lack of policies, lack of integration into the health system, and a lack of awareness and available services. 7,8 Therefore, a feasible PPC service model in the context of limited resources in LMICs is crucially needed. Our children's tertiary hospital is one of the largest pediatric hematology/oncology centers in China.…”
Section: Introductionmentioning
confidence: 99%
“…The barriers and challenges associated with palliative care development for PPC in LMICs include a lack of medical staff, lack of specialist education, lack of policies, lack of integration into the health system, and a lack of awareness and available services. 7,8 Therefore, a feasible PPC service model in the context of limited resources in LMICs is crucially needed. Our children's tertiary hospital is one of the largest pediatric hematology/oncology centers in China.…”
Section: Introductionmentioning
confidence: 99%
“…Departments that frequently applied for urgent neurological consultation included the intensive care unit (ICU), respiratory medicine, cardiovascular medicine, hematology, and nephrology. At present, it is estimated that about 10% of patients present some neurological manifestations in the previous reports [10][11][12][13]. It has been reported that neurological consultation in the ICU is often urgent consultation, which also suggests that patients have more severe diseases to be managed.…”
Section: Discussionmentioning
confidence: 99%
“…Emergency plan evaluation indicator system. Material utilization rate, Staff utilization, Equipment usage rate C 33 Water quality level after disposal, The number of abandoned waters, Damage degree of water transfer project C 41 Technical maturity, Operability, Rationality, Scientific basis, Degree of acceptance C 42 Number of materials and personnel, Allocation rights C 43 Variability, Resilience C 44 Co-movement, Coordination, Communication ability…”
Section: Controllability Of Resource Allocation (C 42 )mentioning
confidence: 99%
“…At present, there are many methods to determine the indicator weight, which can be roughly divided into subjective weighting assessment, objective weighting assessment and combined integration weighting assessment. The subjective weighting method refers to the method of comparing, assigning and calculating the weight of each indicator according to the knowledge and experience or preferences of the decision makers, among which AHP [41,42] and Delphi [43,44] are commonly chosen. The objective weighting method is a method for determining the weight of each indicator based on the difference in objective data of each program evaluation indicator value.…”
Section: Calculation Of the Weights For The Indicatormentioning
confidence: 99%